A dynamic nonlinear model for a wide-load range operation of ultra-supercritical once-through boiler-turbine units. (1st July 2021) - Fan, He; Su, Zhi-gang; Wang, Pei-hong; Lee, Kwang Y.
Abstract: As the penetration of renewable energy generation increases in power grid, ultra-supercritical (USC) once-through boiler-turbine (OTBT) units are required to operate in a wide load range to maintain the grid stability. Coordinated control system (CCS) coordinates boiler and turbine systems to track load demand and ensure safe and economical operation simultaneously. However, few studies focus on modeling the USC-OTBT units for CCS design under the current stringent requirement. This study develops a dynamic nonlinear model of a USC-OTBT unit operating in a wide load range, which is a first step toward designing an effective CCS. This work first analyzes and captures the nonlinear characteristics of the USC-OTBT unit in low load and extends to model the dynamic process of the unit in a wider load range, from low load to full load. Besides, two energy functions are presented by analyzing open-loop responses to improve the model structure and dynamic modeling accuracy. Model structure is derived from mass and energy conservation laws, and model parameters and functions are identified based on running data. Validation results demonstrate the effectiveness of the model for a wide load range operation of the USC-OTBT unit, providing a basis for an effective CCS design. Graphical abstract: Image 1 Highlights: Model can describe the dynamic process of USC units in a wide load range. Two energy functions are built to improve model structure and dynamic accuracy. Model input set points can be generated from output set points. Dynamic parameters in boiler system can be derived from physical information. Model has acceptable dynamic accuracy and can be used for control system design.